Security Issues in Anonymous Communication Systems - Malath Sabri Kareem (LPPM STIE KRAKATAU, 2026)
Purpose: This study examines the security aspects of anonymous communication systems, which are critical for protecting digital privacy and maintaining freedom of expression online. It focuses on widely used systems, such as the Tor network and Holloway's Freedom protocol, analyzing vulnerabilities, systemic weaknesses, and the advanced attack techniques employed by adversaries to compromise user anonymity, including traffic analysis, de-anonymization, and timing correlation attacks. Research Methodology: A literature-based analytical approach was employed, reviewing specialized scientific articles and experimental studies published between 2020 and 2026. Emphasis was placed on research accepted at prominent conferences in network security and privacy protection. The study synthesizes evidence on security threats, attack methodologies, and systemic vulnerabilities affecting anonymous communication systems. Results: The analysis reveals persistent fundamental weaknesses in current anonymous communication systems, which continue to compromise security. Additionally, the application of big data and artificial intelligence has facilitated increasingly sophisticated attack strategies capable of penetrating multiple layers of anonymity. The study identifies both the limitations of existing systems and the emerging risks that users face. Conclusions: Protecting anonymity in digital communication requires both system-level improvements and strategic countermeasures against evolving attack techniques. Recommendations include technical upgrades, protocol redesigns, and adoption of AI-resistant security measures to ensure the resilience of anonymous communication systems in the future. Limitations: The study relies on literature review and secondary data rather than primary experimental validation. As such, conclusions may not fully generalize to all types of anonymous systems or evolving attack scenarios. Contribution: This study provides a comprehensive analysis of current threats and vulnerabilities in anonymous communication systems, offering practical and research-oriented recommendations to strengthen digital privacy protection and to future-proof these systems against increasingly sophisticated attacks.